Microplastic entry into bloodstream via hemodialysis: A dual-simulation clinical study - Yao Deng; Taoping Sun; Zhenheng Long; Xiaoling Luo; Xuyang Geng; Zefang Lin; Chunzhao Chen; Xiaoliang Li (Environmental Pollution, 2026)

Modification Effects of Homologous Recombination Repair Gene Polymorphisms on the Associations Between Urinary Metals and Breast Cancer Risk - Shushu Han; Minjie Lu; Yixin Zhang; Ying Lin; Qiang Liu; Lin Xu; Zefang Ren (Biological Trace Element Research, 2025)

Development of an electrochemical oxidation processes model: Revelation of process mechanisms and impact of operational parameters on process performance - Xinqing Liao; Zefang Chen; Lin Du; Jiawei Chen; Shaohua Chen; John C. Crittenden; Xiaojun Wang (Chemical Engineering Journal, 2025)

Effect mechanism of low-velocity impact loading rate on the failure modes transition of steel-UHPC-steel composite plates - Zefang Wang; Yilinke Tan; Jiachuan Yan; Youzhu Lin; Feng Fan; Qinghua Zhang (Engineering Structures, 2024)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

18β-glycyrrhetinic acid ameliorates MPTP-induced neurotoxicity in mice through activation of microglial anti-inflammatory phenotype - Hanyue Luo; Caishi Zhang; Lujuan He; Zefang Lin; Ji-chun Zhang; Qi Qi; Jia-xu Chen; Wei Yao (Psychopharmacology, 2023)

Experimental study, finite element simulation and theoretical analysis on failure mechanism of steel–concrete-steel (SCS) composite deep beams with UHPC - Youzhu Lin; Jiachuan Yan; Zefang Wang; Chaoying Zou (Engineering Structures, 2023)

Theoretical models and reliability assessment of steel-UHPC-steel composite beams in offshore structures - Youzhu Lin; Jiachuan Yan; Zefang Wang; Chaoying Zou (Ocean Engineering, 2023)

Characterization, risk assessment and resource potential of sediments in the black-odor water in Hunan, China - Jingwei Ma; Xiao Lin; Zefang Yu; Xiang Wang; Jiyi Chen; Qiulai He (Environmental Monitoring and Assessment, 2022)

Geographical and temporal origins of terrestrial vertebrates endemic to Taiwan - Jiekun He; Zefang Gao; Yuanyuan Su; Siliang Lin; Haisheng Jiang (Journal of Biogeography, 2018)
Aim Phylogeographical studies of Taiwan have advanced our knowledge of the origins of its fauna, but the discrepancies raise issues related to the interpretation of single‐taxon studies. Here, we provide a synthesis of the biogeographical histories of multiple terrestrial vertebrates endemic to Taiwan and infer the colonization processes within the context of geological and climatic events. Location Taiwan and neighbouring land masses. Taxon Terrestrial vertebrates. Methods We conducted a meta‐analysis of 28 phylogenetic studies of 33 endemic Taiwanese terrestrial vertebrates to summarize the insights into their source regions and divergence times. We used dispersal–extinction–cladogenesis models to reconstruct the ancestral ranges of 54 endemic species based on a recently published time‐calibrated phylogenetic tree. By constructing a frequency histogram that quantified the number and timing of divergence events within 1 Myr bins, we inferred the spatiotemporal colonization patterns of endemic Taiwanese species. Results The results from 28 phylogenetic studies revealed that South China is the main source region of endemic Taiwanese species. However, based on a more comprehensive time tree, the ancestral area reconstruction analyses indicated that endemic species are predominately of Eastern Himalayan origin. Both datasets highlighted a temporal pattern that the majority of colonization events of terrestrial vertebrates endemic to Taiwan occurred from the early Pliocene ( c . 5 Ma) onwards, and these events were temporally congruent with the geological estimates of the emergence of Taiwan Island. Main conclusions Terrestrial vertebrates endemic to Taiwan reached the island over the last 5 Myr from a variety of zoogeographical regions. In contrast to the traditional notion, the Eastern Himalayas is the most important source region of endemic Taiwanese species, followed by South China and Indochina. In addition to the land bridge, transoceanic dispersal provided another potential mode for species to colonize Taiwan.